2000
DOI: 10.1038/sj.bmt.1702232
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic aspects of invasive Aspergillus infections in allogeneic BMT recipients

Abstract: Summary:To investigate diagnostic aspects of invasive aspergillosis (IA) in allogeneic BMT recipients, the charts of 22 consecutive patients with IA transplanted in 1989-1995 were reviewed. IA was diagnosed 69-466 days (median 131 days) post BMT. In 16 patients (73%), a definite or probable diagnosis of IA was made during life. Respiratory symptoms were the presenting feature in half of the patients followed by neurological symptoms (27%). Chest X-ray revealed single or multiple nodular lesions in 10 patients;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
7

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 28 publications
1
44
1
7
Order By: Relevance
“…In patients with focal pulmonary lesions, a radiologically guided fine-needle biopsy was used as the first-line diagnostic procedure. 19 The diagnosis of IPA was performed using EORTC/ MSG diagnostic criteria as follows. 20 A proven diagnosis of IPA was based on the demonstration of hyphae with microscopy from tissue samples taken with or without a positive culture for Aspergillus sp.…”
Section: Patient Characteristics and Transplantation Proceduresmentioning
confidence: 99%
“…In patients with focal pulmonary lesions, a radiologically guided fine-needle biopsy was used as the first-line diagnostic procedure. 19 The diagnosis of IPA was performed using EORTC/ MSG diagnostic criteria as follows. 20 A proven diagnosis of IPA was based on the demonstration of hyphae with microscopy from tissue samples taken with or without a positive culture for Aspergillus sp.…”
Section: Patient Characteristics and Transplantation Proceduresmentioning
confidence: 99%
“…Previous studies have indicated that CNS aspergillosis may be found in 40-50% of patients with IA. 2,8 Although several reports on CNS aspergillosis have been published, 9-13 most of them include few allogeneic SCT recipients. [14][15][16][17] We have therefore retrospectively analysed the incidence as well as clinical, radiological, and neuropathological findings of CNS aspergillosis among 455 consecutive allogeneic SCT recipients transplanted during a period of 12 years.…”
mentioning
confidence: 99%
“…is the main cause of fungal pneumonia after BMT and its incidence ranges between 4 and 13%. Risk factors described for the development of APA include more than three weeks of corticosteroids therapy, neutropenia and GVHD [4,13]. In the present study, 83% of the patients were in prolonged usage of corticosteroids in the moment of IPA diagnosis, 75% had a confirmed diagnosis of GVHD and 33% were neutropenic.…”
Section: Discussionmentioning
confidence: 63%